Predictors of right ventricular function as measured by tricuspid annular plane systolic excursion in heart failure - Kjaergaard, Jesper (BioMed Central, 2009)
INTRODUCTION: Tricuspid Annular Plane Systolic Excursion (TAPSE) has independent prognostic value in heart failure patients but may be influenced by left ventricular (LV) ejection fraction. The present study assessed the association of TAPSE and clinical factors, global and regional LV function in 634 patients admitted for symptomatic heart failure. METHODS & RESULTS: TAPSE were correlated with global and regional measures of longitudinal LV function, segmental wall motion scores and measures of diastolic LV function as measured from transthoracic echocardiography. LV ejection fraction, wall motion index scores, atrio-ventricular annular plane systolic excursion of the mitral annulus were significantly related to TAPSE. Septal and posterior mitral annular plane systolic excursion (β = 0.56, p < 0.0001 and β = 0.35, p = 0.0002 per mm, respectively) and non-ischemic etiology of heart failure (β = 1.3, p = 0.002) were independent predictors of TAPSE, R(2 )= 0.28, p < 0.0001. The prognostic importance of TAPSE was not dependent of heart failure etiology or any of the other clinical factors analyzed, p(interaction )= NS. CONCLUSION: TAPSE is reduced with left ventricular dysfunction in heart failure patients, in particular with reduced septal longitudinal motion. TAPSE is decreased in patients with heart failure of ischemic etiology. However, the absolute reduction in TAPSE is small and seems to be of minor importance in the clinical utilization of TAPSE whether applied as a measure of right ventricular systolic function or as a prognostic factor.